1990
DOI: 10.1159/000205032
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism in Patients with Thalassemia Syndromes

Abstract: Sixty transfusion-dependent thalassemic patients were studied by simultaneous measurement of circulating thyroid hormones, basal thyroid-stimulating hormone (TSH) and TSH response to thyrotropin-releasing hormone with the aim of evaluating the frequency of hypothyroidism in such patients, and the relationship between hypothyroidism and compliance with treatment and iron overload. Thyroid failure was present in 31 of the 60 patients. A correlation was found between impairment of thyroid functions, duration of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
2
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 6 publications
4
18
2
5
Order By: Relevance
“…This is contrary to previous studies [71,72] including a 12-year longitudinal study by Filosa et al [72] 7 years earlier which showed no association between ferritin levels or transfusion statuswith worsening thyroid function. Some studies have reported a high prevalence of primary hypothyroidism reaching up to 17% -18% [7,73] whereas others have reported a low prevalence of 0% -9% [74,75]. Shamshirsaz et al [1] demonstrated a prevalence of 7.7% in their study similar to the Italian study group [35] who found 6.2% patients to be hypothyroid where as Aydinok et al [47] showed the prevalence to be higher at 16%.…”
Section: Open Access Ojemdmentioning
confidence: 73%
“…This is contrary to previous studies [71,72] including a 12-year longitudinal study by Filosa et al [72] 7 years earlier which showed no association between ferritin levels or transfusion statuswith worsening thyroid function. Some studies have reported a high prevalence of primary hypothyroidism reaching up to 17% -18% [7,73] whereas others have reported a low prevalence of 0% -9% [74,75]. Shamshirsaz et al [1] demonstrated a prevalence of 7.7% in their study similar to the Italian study group [35] who found 6.2% patients to be hypothyroid where as Aydinok et al [47] showed the prevalence to be higher at 16%.…”
Section: Open Access Ojemdmentioning
confidence: 73%
“…Thyroid dysfunction has been reported in 13–60% of patients with thalassemia, but its severity is variable in different series. Some studies reported a high prevalence of primary hypothyroidism, reaching up to 17–18% [18,19], While others reported low prevalence of 0–9% [20,21]. It is important to note that even in the studies in which the prevalence of overt hypothyroidism as a complication of thalassemia major is relatively low, milder forms of thyroid dysfunction are much more common [18,20,22], though again there are wide variations in different reports.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported a high prevalence of primary hypothyroidism, reaching up to 17–18% [18,19], While others reported low prevalence of 0–9% [20,21]. It is important to note that even in the studies in which the prevalence of overt hypothyroidism as a complication of thalassemia major is relatively low, milder forms of thyroid dysfunction are much more common [18,20,22], though again there are wide variations in different reports. These discrepancies can not be attributed to differences in patients' ages, but rather to difference treatment protocols, including differing transfusion rates and chelation therapies [21].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoxia due to anaemia, viral infections and individual susceptibility are other factors which could potentiate the toxicity of iron deposition and contribute to endocrine dysfunction. 2,3 Detecting the exact prevalence of endocrinopathies in patients with thalassaemia is challenging due to variability in the study population. This partly relates to ages of patients being studied and the adequacy of chelation therapy.…”
Section: Introductionmentioning
confidence: 99%